PENINGKATAN KEMAMPUAN TEKNIK MENGAJAR BAHASA INDONESIA PADA MAHASISWA IKIP PGRI JEMBER MELALUI METODE DISKUSI KELOMPOK KECIL DAN MEDIA GAMBAR - Nurhafit Kurniawan (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2019)
Most of the students of the PG PAUD PGRI JEMBER Study Program, still do not have the ability to make greeting sentences, congratulations, thanks, and apologies. This study aims to explain the process of increasing the ability to use Indonesian in making sentences greeting and increasing the ability to use Indonesian in making sentences. This study was designed as an action research with two cycles. Data analysis used descriptive analysis with both qualitative and quantitative approaches (percentages). The research findings show that the learning process by using small group discussion methods and image media has run quite effectively. Likewise, the ability of students to make sentences also increases, both individually and classically. The conclusion of the research shows that the method of small group discussion and image media can be applied by students to be able to improve students' abilities in making greeting sentences, congratulations, thanks, and apologies